Estimation of Paddy Productivity at Subdistrict Level using Geoadditive Small Area Estimation Model in Ponorogo Regency - Maulana, Arswenda Putra; Prasetyo, Rindang Bangun (Department of Statistics ITS, 2024)
Paddy is the most important food crop in the world and it is the source of food needed by more than half of the population on a global scale. However, the world is experiencing the threat of a food crisis, so the Indonesian government continues to be committed to increasing national paddy production and ensuring food sufficiency in the country by implementing food self-sufficiency programs in each region. Paddy productivity data can be used as one of the government's benchmarks to assess the success of the food self-sufficiency program, but BPS-Statistics Indonesia only provides data on paddy productivity up to the district/cities level. Therefore, this study aims to estimate paddy productivity at sub-district level using the Geo-SAE method. Based on the research results, the estimation of the average paddy productivity in Ponorogo Regency in 2022 using Geo-SAE was obtained at 5.8 tons/ha and resulted in a smaller RSE value compared to the direct estimation at sub-district level. This indicates that the Geo-SAE method has better precision than the direct estimation method. Meanwhile, additional result from estimation of paddy productivity shows that in Ponorogo Regency in 2022 there is a large rice surplus. Therefore, it can be said that Ponorogo Regency is experiencing a very good food sufficiency condition.